In vitro activities of licochalcone A against planktonic cells and biofilm of Enterococcus faecalis - Liu, Xiaoju; Xiong, Yanpeng; Shi, Yiyi; Deng, Xiangbin; Deng, Qiwen; Liu, Yansong; Yu, Zhijian; Li, Duoyun; Zheng, Jinxin; Li, Peiyu (Frontiers in Microbiology, 2022)
This study aims to evaluate the in vitro antibacterial and anti-biofilm activities of licochalcone A on Enterococcus faecalis, and to investigate the possible target genes of licochalcone A in E. faecalis. This study found that licochalcone A had antibacterial activities against E. faecalis, with the MIC50 and MIC90 all were 25 μM. Licochalcone A (at 4 × MIC) indicated rapid bactericidal effect on E. faecalis planktonic cells, and killed more E. faecalis planktonic cells (at least 3-log10 cfu/ml) than vancomycin, linezolid, or ampicillin at the 2, 4, 6 h of the time-killing test. Licochalcone A (at 10 × MIC) significantly reduced the production of E. faecalis persister cells (at least 2-log10 cfu/ml) than vancomycin, linezolid, or ampicillin at the 24, 48, 72 and 96 h of the time-killing test. Licochalcone A (at 1/4 × MIC) significantly inhibited the biofilm formation of E. faecalis. The RNA levels of biofilm formation-related genes agg, esp, and srtA markedly decreased when the E. faecalis isolates were treated with licochalcone A at 1/4 × MIC for 6 h. To explore the possible target genes of licochalcone A in E. faecalis, the licochalcone A non-sensitive E. faecalis clones were selected in vitro by induction of wildtype strains for about 140 days under the pressure of licochalcone A, and mutations in the possible target genes were detected by whole-genome sequencing. This study found that there were 11 nucleotide mutations leading to nonsynonymous mutations of 8 amino acids, and among these amino acid mutations, there were 3 mutations located in transcriptional regulator genes (MarR family transcriptional regulator, TetR family transcriptional regulator, MerR family transcriptional regulator). In conclusion, this study found that licochalcone A had antibacterial effect on E. faecalis, and significantly inhibited biofilm formation of E. faecalis at subinhibitory concentrations.